REVIEWS (Heythrop journal, 1974)
Books Reviewed in this Article: God is not yet Dead. By Vitězslav Gardavsky. Pp. 224, Harmondsworth Penguin Books, 1973, £0.45. The Persistence of Religion. By Andrew M. Greeley. Pp. 280, London, SCM Press, 1973, £2.80. The Ghost Dance, Origins of Religion. By Weston La Barre. Pp. xvi, 677, London, Allen and Unwin, 1972, £6.95. Philosophy of Religion: The Historic Approaches. By M. J. Charlesworth. Pp. xiv, 216, London, Macmillan, 1972, £2.95. Scepticism. By Kai Nielsen. Pp. x, 118 (New Studies in the Philosophy of Religion), London, Macmillan, 1973, £2.50. The Edges of Language. By Paul van Buren. Pp. 178, London, SCM Press 1972, £2.50 Ludwig Wittgenstein: Philosophy and Language. Edited by Alice Ambrose and Morris Lazerowitz. Pp. 325, London, George Allen and Unwin, 1972, £5.25. Organized Religion according to Dr S. Radhakrishnan. By Thomas Paul Urumpackal. Pp. xx, 283 (Analecta Gregoriana 184), Rome, Gregorian University Press, 1972, no price given. The Problems of Religious Faith. By James P. Mackey. Pp. 344, Dublin, Helicon, 1972, £5.60. Christianity an End to Magic. By John Baptist Walker. Pp. viii, 118, London, Darton, Longman and Todd, 1972, £1.75. Every Day God: Encountering the Holy in World and Worship. By J. G. Davies. Pp. ix, 386, London, SCM Press, 1973, £3.75. The Liturgy of Comprehension 1689. By Timothy J. Fawcett. Pp. xii, 287 (Alcuin Club Collections No. 54), Southend-on-Sea, Mayhew-McCrimmon 1973, £4.00. Hegel's Development Towards the Sunlight, 1770-1801. By H. S. Harris. Pp. xxxii, 574, Oxford, Clarendon Press, 1972, £5.00 Hegel. By Raymond Plant. Pp. 214 (Political Thinkers 1), London, George Allen and Unwin, 1973, £3.75. Hegel's Theory of the Modern State. By Shlomo Avineri. xi, 252(Cambridge Studies in the History and Theory of Politics), Cambridge, Cambridge University Press, 1972, £3.40. Opuscula Selecta: Classica, Hellenistica, Christiana. By G. Zuntz. Pp. vii, 322, Manchester, Manchester University Press, 1972, £4.80. Die theologische Mitte des ersten Klemensbriefes. By Gerbert Brunner. Pp. ix, 177 (Frankfurter theologische Studien 1), Frankfurt, Josef Knecht, 1972, no price given. Tertullian: Adversus Marcionem, Books I-III Books IV-V. Edited and translated by Ernest Evans. Pp. xxiii, 658 (Oxford Early Christian Texts), Oxford, The Clarendon Press, 1972, £8.00 for the set of two volumes. Guillaume de Saint-Amour et la polémique universitaire parisienne 1250-1259. By M. -M. Dufeil. Pp. xxxii 467, Paris, Éditions A. et J. Picard, 1972, 55F. Themes and Images in the Medieval English Religious Lyric. By Douglas Gray. Pp. 300, London, Routledge and Kegan Paul, 1972, £4.00. Shakespeare's God: The Role of Religion in the Tragedies. By Ivor Morris. Pp. 496, London, George Allen and Unwin, 1972, £7.75. Racine. By Lucien Goldmann, translated by Alastair Hamilton. Pp. xxii, 105, Cambridge, Rivers Press, 1973, £2.25. Sigmund Freud and Lou Andreas-Salomé. Letters. Edited by Ernst Pfeiffer. Pp. 244, London, Hogarth Press, 1972, £3.75. Encyclopaedia of Psychology. Edited by H. J. Eysenck, W. Arnold and R. Meili. 3 volumes, London, Search Press, 1972, £8.00 per volume. Induction and Intuition in Scientific Thought. By B. P. Medawar. Pp. ix, 62, London, Methuen, 1969, £0.80.